IMPACT OF HYPERLOCAL MEDIA ON LOCAL COMMUNITIES - Murinska, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Nowadays one of the channels to get information about the local environment is hyperlocal news media. It is another way to reach an audience online,  as a number of users of local television, radio and newspapers is decreasing. Hyperlocals come in many different forms, but their main characteristics show them as a news source. Hyperlocal news media have much in common with weekly community newspapers – these sites focus on a small, geographically defined area, as theoretical literature about local media say. Such news sites are becoming an important part of information space because of their fastness, digital possibilities and variety of content authors. Thus, uncertainty of staff raises questions about values, behaviours and ethics of journalism.The aim of the paper is to examine the types and functions of hyperlocal news media to clarify what kind of content is produced in hyperlocal news media and what their role is in a local community in Latvia. There were seven Latvian hyperlocal news websites analysed; the quantitative and qualitative content analysis was made to explore research questions.An analysis of the content of the hyperlocal news media showed that it was primarily an initiative of people working in the media, not an initiative of the people themselves. Hyperlocal news media mainly inform about what is happening in the city, municipality or village, but community involvement is minimal. Overall, function to give information dominates, but the personification with the local community is not common, so it is difficult for the community to identify themselves with the media, and thus with the community.